2008
DOI: 10.1152/ajpheart.00986.2007
|View full text |Cite
|
Sign up to set email alerts
|

Moderate hypothermia increases the chance of spiral wave collision in favor of self-termination of ventricular tachycardia/fibrillation

Abstract: I. Moderate hypothermia increases the chance of spiral wave collision in favor of self-termination of ventricular tachycardia/fibrillation. Am J Physiol Heart Circ Physiol 294: H1896-H1905, 2008. First published February 29, 2008 doi:10.1152/ajpheart.00986.2007.-In cardiac arrest due to ventricular fibrillation (VF), moderate hypothermia (MH, 33°C) has been shown to improve defibrillation success compared with normothermia (NR, 37°C) and severe hypothermia (SH, 30°C). The underlying mechanisms remain unclear.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
29
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 26 publications
4
29
2
Order By: Relevance
“…28 Using a clinically applicable temperature (30°C), we observed that TH decreased CV, shortened WL, and enhanced APD dispersion and spatial heterogeneity of CT -1 restitution, consistent with the results reported by Harada et al in a 2-dimensional rabbit ventricle at TH (30°C). 12 The only difference was that Harada et al reported that the maximal slope of APDR significantly increased, 12 whereas we found no difference among baseline, TH (30°C) and rewarming.…”
Section: Electrophysiological Properties During Th (30°c)contrasting
confidence: 82%
See 2 more Smart Citations
“…28 Using a clinically applicable temperature (30°C), we observed that TH decreased CV, shortened WL, and enhanced APD dispersion and spatial heterogeneity of CT -1 restitution, consistent with the results reported by Harada et al in a 2-dimensional rabbit ventricle at TH (30°C). 12 The only difference was that Harada et al reported that the maximal slope of APDR significantly increased, 12 whereas we found no difference among baseline, TH (30°C) and rewarming.…”
Section: Electrophysiological Properties During Th (30°c)contrasting
confidence: 82%
“…10, 11 Harada et al found that in 2-dimensional rabbit ventricular preparations, TH (30°C) enhanced wavebreaks and regeneration of new spiral waves during VF, facilitating the maintenance of ventricular tachycardia (VT) and VF. 12 While using a clinically appropriate temperature of 32-34°C, they demonstrated that the spiral waves of VT/VF frequently collided and dissipated in favor of self-termination of VT/VF, a different effect from that of TH at 30°C. 12 Whether the wavefront characteristics (ie, wavebreaks) of VF in this 2-dimensional model also occur in 3-dimensional intact hearts at TH (30°C) remains unclear.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4, 26 Other studies investigating the effect of TH on ventricular conduction did not explore GJ remodeling. 5 In this study, we investigated the conduction properties and Cx43 GJ remodeling specifically in the therapeutic range of hypothermia (33°C and 30°C) in non-hibernating rabbit hearts.…”
Section: Cx43 Remodeling During Thmentioning
confidence: 99%
“…And at lower temperature (deeper hypothermia 5.9 • C ± 1.3 • C), local cooling facilitates termination of spiral waves [54]. The latter two studies [54,53] showed the positive effect of hypothermia in macro / organ scale.…”
Section: Resultsmentioning
confidence: 90%